Using computer bulletin boards - Hedtke, John V. ([S.l.] : Mis Pr, 1994)
This updated introduction to the basics and finer points of PC bulletin board services, combines features of a tutorial with a desk reference. It provides instructions for downloading and uploading files and includes tips on modern configuration and communication and file transfer protocols. It covers the basics of logging on, exploring and logging off computer BBSs and introduces readers to the Internet, CompuServe and America Online with navigational aids and tips on e-mail, forums and customs and protocols.